The creation and the design of the natural order: a thematic reading of selected verses of the Qur’an - Hashi, Abdurezak Abdulahi (2015)
The Qur’an which is, together with the Prophetic teachings, forms the founding scripture of the Islamic teachings, constitutes the divine message that is set to guide man to what ought to be. Though the Qur’an is not a book of chemistry nor is it a theory of physics, however its teachings incorporated thought provoking expressions about the formation and the design of the universe. This paper uses thematic and textual analysis, and attempts to expose selected verses of the Qur’an about the natural order, with particular emphasis on the concept of creation and the design of the natural order. For this paper represents a thematic analysis of selected verses of the Qur’an, debates of theologians and philosophers on evolution versus creation of the universe, would not be included